2021
DOI: 10.3389/fcvm.2021.647806
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of m6A RNA Methylation in Heart Failure With Preserved Ejection Fraction

Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous disease, in which its pathogenesis is very complex and far from defined. Here, we explored the N6-methyladenosine (m6A) RNA methylation alteration in patients with HFpEF and mouse model of HFpEF.Methods: In this case–control study, peripheral blood mononuclear cells (PBMCs) were separated from peripheral blood samples obtained from 16 HFpEF patients and 24 healthy controls. The change of m6A regulators was detected by quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…The included studies were published between 2007 and 2021. Twenty-three studies were conducted in China [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; ten in the United States [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; five in Iran [ 47 , 48 , 49 , 50 , 51 ]; four in Italy [ 52 , 53 , 54 , 55 ]; three in the Netherlands [ 56 , 57 , 58 ]; three in Germany [ 59 , 60 , 61 ]; two in Taiwan [ 62 , 63 ]; two in Australia [ 64 , 65 ]; and one each in New Zealand [ 66 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were published between 2007 and 2021. Twenty-three studies were conducted in China [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; ten in the United States [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; five in Iran [ 47 , 48 , 49 , 50 , 51 ]; four in Italy [ 52 , 53 , 54 , 55 ]; three in the Netherlands [ 56 , 57 , 58 ]; three in Germany [ 59 , 60 , 61 ]; two in Taiwan [ 62 , 63 ]; two in Australia [ 64 , 65 ]; and one each in New Zealand [ 66 …”
Section: Resultsmentioning
confidence: 99%
“…Five of the included studies reported the change of DNA methylation in HF [ 25 , 35 , 60 , 64 , 70 ]. All of them examined the DNA methylation pattern using peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study of RNA modifications, epitranscriptomics remains in its infancy, methodological breakthroughs of the last decade have enabled identification of these modifications with such accuracy that their large-scale screening is rational [ 117 , 118 , 119 , 120 , 121 , 143 ]. Encouragingly, research findings suggest both m 6 A and A-to-I to act as contributors or even potential initiators and drivers for several cardiovascular physiological and pathological processes including cardiogenesis, angiogenesis, hypertension, hypertrophy, atherosclerosis, ischemia, ischemia-reperfusion, fibrosis, HF, congenital heart disease, stroke, aneurysms, as well as cardiac repair and regeneration [ 25 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 51 , 52 , 53 , 54 , 55 , 56 ]. Remarkably, the first indication for coronary atherosclerosis to be reflected in the m 6 A content of mRNAs and long non-coding RNAs of peripheral mononuclear cells with suggested involvement in its pathophysiology has just recently been reported [ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing or overexpression of enzymes controlling m 6 A abundance has revealed the role of m 6 A in driving immune reactivity, proliferation, apoptosis, and many intracellular processes including mRNA splicing, translation, and degradation [ 20 , 26 ], as well as miRNA biogenesis [ 27 ]. Moreover, reports from diverse fields of research [ 28 , 29 , 30 , 31 ], and in an array of cardiovascular pathologies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], provide evidence of m 6 A as a master post-transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%